EXTENT OF TEACHERS INVOLVEMENT IN SECONDARYSCHOOLADMINISTRATION IN ENUGU STATE (NAU Journal of Technology and Vocational Education, 2024)
The study centered on the extent to which teacher’s are involved in decision making in secondaryschool administration in Enugu State. Two research questions were raised and two null hypotheseswere formulated to guide the study. The population consists of 4520 female teachers and 2410 maleteachers, giving a total of 6930 secondary school teachers. The sample consist of 692 teachers, whichwas selected through a stratified random sampling procedure. A structure questionnaire was designedto elicit appropriate information from the respondents. The instrument was faced validated by threeexperts, two from educational management department and one in measurement and evaluationdepartment all from faculty of education in Enugu State University of Science and Technology. Thereliability co-efficient of the instrument was calculated using Cronbach alpha method. Alpha valuewas found to be 0.86 indicating high reliability of the instrument. Mean rating were used to answersthe research questions, and t- test statistics was used to test the hypotheses at 0.5 level of significance. The Findings of this study indicates that teachers are involved to a great extent in decision-makinginsecondary schools administration in Enugu state. The authors recommended among others that Schooladministrators should endeavour to always involve teachers in any decision-making that will affectthem and make them to be part of any decision-making in the school system.
Keywords: Business administration, decision-making, Involvement, secondary schools